Inside Back Cover: Solar Thermochemical Energy Storage Through Carbonation Cycles of SrCO3/SrO Supported on SrZrO3 (ChemSusChem 22/2015). Issue 22 (9th November 2015) - Rhodes, Nathan R.; Barde, Amey; Randhir, Kelvin; Li, Like; Hahn, David W.; Mei, Renwei; Klausner, James F.; AuYeung, Nick
Abstract : The Inside Back Cover picture shows a concept for dispatchable solar thermochemical energy storage. The chemistry demonstrated here features a discharge step at 115°C, which has the potential to enable high efficiency, cost‐effective power generation using a combined cycle. More details can be found in the Full Paper by N. AuYeung et al. onpage 3793 in Issue 22, 2015 (DOI:10.1002/cssc.201501023 ).